Considerations and opportunities for multilevel HPV vaccine communication interventions. Issue 2 (23rd November 2021) - Oh, April; Gaysynsky, Anna; Winer, Rachel L; Lee, Hee Y; Brewer, Noel T; White, Arica
Abstract : From 2016 to 2019, the National Cancer Institute and the Centers for Disease Control and Prevention funded three Special Interest Projects focused on developing and testing multilevel HPV vaccination communication interventions. In this commentary, we highlight lessons learned from the funded projects, including the importance of engaging community members in the early stages of the research process, the challenges of evaluating multilevel interventions, and the need to consider stakeholder implementation preferences.